2015 ASEE Annual Conference and Exposition Proceedings
DOI: 10.18260/p.23494
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Expertise and its Manifestation in CAD Modeling: A Comparison of Practitioners and Students

Abstract: The state of Computer-Aided Design (CAD) education is often decried for focusing too much on the low-level skills required to do specific tasks; this often comes at the expense of promoting the strategic knowledge associated with expertise. The environment that today's students will encounter in the workplace will require them to adapt to new challenges in innovative ways. Namely, they will need to become adaptive experts. To better inform CAD education, this work examines how practicing engineers adapt to a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…In all other subscales, there was no significant difference in AE scores. This result is in line with that reported by prior researchers [18] where CAD practitioners (n=14) were compared to students in a CAD course (n=92) and also displayed statistically significant differences only in the category of multiple perspectives where practitioners again outscored the undergraduate students. While more data is required to further validate these findings, the correlation between the results found here and in prior work do identify a potential gap in the category of MP between students and working professionals.…”
Section: Figure 3: Comparison Of Ae Levels Displayed By Undergraduate...supporting
confidence: 91%
See 1 more Smart Citation
“…In all other subscales, there was no significant difference in AE scores. This result is in line with that reported by prior researchers [18] where CAD practitioners (n=14) were compared to students in a CAD course (n=92) and also displayed statistically significant differences only in the category of multiple perspectives where practitioners again outscored the undergraduate students. While more data is required to further validate these findings, the correlation between the results found here and in prior work do identify a potential gap in the category of MP between students and working professionals.…”
Section: Figure 3: Comparison Of Ae Levels Displayed By Undergraduate...supporting
confidence: 91%
“…More recently, Fisher (co-author of the AE survey) and colleagues have been reporting data concerning AE levels displayed by undergraduate STEM students at a private university [16], and have detailed growth in AE levels among low-income students in particular as they progress through their course of study [17]. Only one study (to our knowledge) has compared the levels of AE displayed by students with working professionals [18]. In this work, the survey of Fisher and Peterson was used to examine AE levels displayed by students in a CAD course and CAD practitioners.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, this same research team compared student and practicing engineer manifestations of adaptive expertise via the Fisher-Peterson AE survey instrument as well as through coded pre-and post-interview responses. Similar to the results from the initial Fisher and Peterson (2001) work, their results indicated that the practicing engineers had more "multiple perspectives" and more overall manifestations of adaptive expertise than students (Ozturk, 2015). Other researchers have also examined the applicability of using the concept of adaptive expertise to gauge student development in undergraduate CAD and design courses (Kuo, 2018;Ramos Barbero, 2018).…”
Section: Applications Of the Concept Of Adaptive Expertisementioning
confidence: 63%
“…Both definitions have been used in prior work and a consensus on the correct representation of AE has yet to be established. It is generally accepted, however, that the dimensions of adaptiveness, based on either definition, are rarely taught explicitly in undergraduate engineering programs [9][10][11][12].…”
Section: What Is Adaptive Expertise?mentioning
confidence: 99%
“…A paucity of data concerning levels of AE displayed by various populations was also observed. Fortunately, a survey instrument [14], originally developed in 2001, was found to still be in use as a tool for measuring AE, and various studies had indicated its reliability [9], [15]. Based on this review of the literature, the definition of Adaptive Expertise and the survey for its measurement put forward by Fisher and Peterson [16] was chosen for this work.…”
Section: What Is Adaptive Expertise?mentioning
confidence: 99%